Development process for tar filtering from biomass pyrolysis - Naili Rozan, Alya; Purwanto, Hadi (2015)
This paper presents a new approach for recovering tar produced from biomass pyrolysis process. Pyrolysis is a promising thermochemical process to utilize biomass to produce gas, char and tar. Tar is a vapour/liquid product containing carbon, and it is often found in producer gas. It needs to be recovered from gas mixture to upgrade its value for the tar to be utilized on its own as a fuel source. In this developed process, steelmaking slag and low-grade iron ore were made porous by dehydration process, and were then introduced as a tar filter to trap tar produced during biomass pyrolysis. The purpose of this work is to investigate the possibility of using porous materials for tar filtering during pyrolysis process. Tar vapour infiltrated within the porous materials and then decomposed into carbon and gases where carbon was deposited on the pore surface. Clean gas can be collected and tar can be recovered before being utilized as a renewable energy source by itself. After the trapping process, carbon was found to be deposited within the porous material. The product of the tar filtering will be carbon-deposited material – a potential candidate to be used as a renewable fuel source.